2018
DOI: 10.1002/erv.2623
|View full text |Cite
|
Sign up to set email alerts
|

The importance of body image disturbances for the outcome of outpatient psychotherapy in patients with anorexia nervosa: Results of the ANTOP‐study

Abstract: This study investigates the role of body image self-appraisal in predicting the outcomes of outpatient psychotherapy in patients with anorexia nervosa (AN). Multiple linear regression analyses and a path-analysis model were applied to test the study hypotheses that body image at baseline predicts treatment outcomes of outpatient psychotherapy in patients with AN at follow-up measurement. The analyses were conducted as secondary analyses in a subgroup (n = 148) of the anorexia nervosa treatment of outpatient-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 25 publications
4
31
0
3
Order By: Relevance
“…Yet, the current data analysis revealed that the Body Image module was surprisingly the least frequently used module among the ANTOP therapists; specifically, it was used in less than 3% of sessions. The current findings provide evidential support for the concern that body image disturbances are somewhat neglected in eating disorder therapy [ 4 , 28 ]. Accordingly, treatment outcomes might be improved by placing more focus on body image disturbances [ 25 ].…”
Section: Discussionsupporting
confidence: 66%
“…Yet, the current data analysis revealed that the Body Image module was surprisingly the least frequently used module among the ANTOP therapists; specifically, it was used in less than 3% of sessions. The current findings provide evidential support for the concern that body image disturbances are somewhat neglected in eating disorder therapy [ 4 , 28 ]. Accordingly, treatment outcomes might be improved by placing more focus on body image disturbances [ 25 ].…”
Section: Discussionsupporting
confidence: 66%
“…Current studies (e.g. Brockmeyer et al, ; Junne et al, ; Mölbert et al, ) point out the importance of cognitive‐affective rather than sensory‐perceptual body image/schema disturbances in AN. Following this evidence, it would be indicated to start with BI interventions early (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Another possible direction is the identification of treatment components/techniques that should be conducted together with BI interventions. Given, for example, the strong relationship between affective symptoms, stress and BI in patients with AN (Junne et al, ) the combination of BI directed interventions with stress reduction programs are advisable.…”
Section: Discussionmentioning
confidence: 99%
“…Eine Therapieevaluation der ambulanten Psychotherapie bei Anorexia nervosa im Rahmen der multizentrisch durchgeführten ANTOP-Studie hat gezeigt, dass negatives Körperbild mit erhöhtem Angst-und Stresserleben assoziiert und ein relevanter Prädiktor für die Gewichtszunahme in der Therapie ist [6,7]. Weitere Auswertungen haben ergeben, dass das Körperbild in dieser Patientenkohorte kaum explizit in den Therapien adressiert wurde [8].…”
Section: Grundlagenunclassified